Tawaran: Layanan Bimbingan Kelompok Islami Melalui Pendekatan Behavior Untuk Meningkatkan Disiplin Belajar Siswa - Sopiah, Ai Durotus; Nurjannah (Jurnal Bimbingan dan Konseling Islam, 2023)
Guidance and counseling teachers are important. This looks at the various cases and problems that exist in the world of education. Students should be children who try to explore all the potential they have, but each student's journey to seek knowledge will never be smooth and perfect. Student learning discipline is an aspect that is desired by every supervisor or educator. However, it cannot be denied that student learning indiscipline exists in every school. The cause of this indiscipline is due to the lack of awareness of students as students. The reflection that can be highlighted from students is their visible behavior. Students' lack of learning discipline is important to address. There are many ways to improve student learning discipline. Likewise, the techniques used to improve discipline. The offer put forward as an intervention in improving student learning discipline is of course Islamic group guidance through a behavioral approach suitable for use.